2019
DOI: 10.1016/j.pmedr.2019.100999
|View full text |Cite|
|
Sign up to set email alerts
|

Crisis text patterns in youth following the release of 13 Reasons Why Season 2 and celebrity suicides: A case study of summer 2018

Abstract: HighlightsCTL is a national resource that provides text message counselling for people in crisis.Use of CTL, increased following the release of 13RW2 and celebrity suicides.CTL-use was significantly higher following celebrity deaths than the release of 13RW2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…Other studies mentioned by Mueller herself back up both arguments: regarding the former, Cooper et al (2018) confirmed an increased amount of admissions at a children's hospital for cases of self-inflicted harm; and, as for the latter, Thompson et al (2019) found out that there was a significant growth in the messages to the Crisis Text Line after the release of the first season. In a similar line, Sugg et al (2019) ran a quasi-experimental study that highly coincided with Thompson et al's postulates and revealed «a significant relationship between highly publicised celebrity deaths by suicide, and media portrayals of suicide and help-seeking patterns among young people» after the release of 13 Reasons Why's second season.…”
Section: State Of the Artmentioning
confidence: 83%
“…Other studies mentioned by Mueller herself back up both arguments: regarding the former, Cooper et al (2018) confirmed an increased amount of admissions at a children's hospital for cases of self-inflicted harm; and, as for the latter, Thompson et al (2019) found out that there was a significant growth in the messages to the Crisis Text Line after the release of the first season. In a similar line, Sugg et al (2019) ran a quasi-experimental study that highly coincided with Thompson et al's postulates and revealed «a significant relationship between highly publicised celebrity deaths by suicide, and media portrayals of suicide and help-seeking patterns among young people» after the release of 13 Reasons Why's second season.…”
Section: State Of the Artmentioning
confidence: 83%
“…Online activity, including social media, has been highlighted as a possible risk factor for suicide, especially among young people (Luby and Kertz 2019;Massing-Schaffer and Nesi 2020). The suicide contagion effect is well documented (Velting and Gould 1997;Daine et al 2013;Joiner Jr 1999); exposure to suicide-related information is associated with increased suicide prevalence, including both fictional (Sugg et al 2019;Niederkrotenthaler et al 2019;Sinyor et al 2019;Ayers et al 2017) and real (Joiner Jr 1999;Won et al 2013;Sisask and Värnik 2012) accounts of suicide deaths. Individuals who specifically seek self-harm or suicide-related content may be at especially high risk for this contagion (Sedgwick et al 2019;Mars et al 2015;Daine et al 2013).…”
Section: Self-harm and The Internetmentioning
confidence: 99%
“…A great need exists to train and support clinicians to go to people's online presence. Among support options, CTL in particular is accessed at higher rates during population-wide stressors, such as exposure to fictional suicides (e.g., 13 Reasons Why), media coverage of suicide deaths of celebrities (e.g., Anthony Bourdain), [65] and climate-related disasters. [66] For example, after Hurricane Florence in 2018, CTL crisis text volume in North and South Carolina, USA, showed an immediate, sustained increase in crisis texts about stress/anxiety and suicidal thoughts in the six weeks following the weather-related disaster.…”
Section: Opportunities To Transform Service Deliverymentioning
confidence: 99%